Rhétorique émotionnelle et précarité dans le travail social - Charlène Charles (La Nouvelle Revue du Travail)
This study of the emotions felt by youth educators working for France’s Aide Sociale à l'Enfance Child Welfare Organisation shows the control and prescriptions to which they have been subjected. At the same time, such emotions can be used as a way of getting around or resisting institutional emotional norms. The article demonstrates how the emotional norms characterising the social sector can be destabilised by the variability of wage levels and greater work flexibility that socio-educational staff workers must contend with nowadays. Lastly, it also shows how emotional manifestations (and the way that emotions are presented) can become factors of internal competitiveness in this profession, affecting its very definition.